2010
DOI: 10.1038/jes.2010.20
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to 50 Hz magnetic fields in apartment buildings with indoor transformer stations in Israel

Abstract: To advance our understanding of an association between exposure to power frequency magnetic fields (MFs) and the risk of childhood leukemia, we should conduct a study that is convincingly free of selection and response bias, with highly accurate exposure assessment and a large number of highly exposed individuals. Previous measurements revealed that MF in apartments located above internal transformer stations (ITSs) are higher than in other apartments in the same building. An international epidemiologic study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 11 publications
1
8
1
1
Order By: Relevance
“…The number of spaces where it has been measured is indicated, and finally the average value of the measurements made in the bed or beds of the most affected spaces are also presented. Our measurements are within the order of magnitude of the measurements carried out in Finland, Switzerland, Hungary, Israel, Bulgaria, and The Netherlands [10][11][12][13][14][15][16][17][18], in the framework of the TransExpo Project [15]. The average of the average values gives us an average value of 0.4 µT for the dwellings above or adjacent to the TS.…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…The number of spaces where it has been measured is indicated, and finally the average value of the measurements made in the bed or beds of the most affected spaces are also presented. Our measurements are within the order of magnitude of the measurements carried out in Finland, Switzerland, Hungary, Israel, Bulgaria, and The Netherlands [10][11][12][13][14][15][16][17][18], in the framework of the TransExpo Project [15]. The average of the average values gives us an average value of 0.4 µT for the dwellings above or adjacent to the TS.…”
Section: Resultssupporting
confidence: 53%
“…This would greatly facilitate environmental and epidemiological studies, eliminate the control selection biases, and eliminate confounding agents, such as the ionized air surrounding the high-voltage cables, which would not be present in the dwellings attached to the TSs. Measurement campaigns have been carried out in Finland, Israel, Hungary, and Switzerland to analyze a possible exposure assessment procedure (Ilonen et al [10]; Hareuveny et al [11]; Szabo et al [12]; Thuroczy et al [13]; Martin Rösli et al [14]); in these works, in the framework of the TransExpo project [15][16][17][18], specific measurements have been made in apartments in buildings on which TSs are located on the ground floor.…”
Section: Introductionmentioning
confidence: 99%
“…Conducted measurements for the pilot TRANSEXPO study, show a clear distinction between the magnetic field values in the "exposed" apartments and all other apartments located on same buildings [6,7,8]. The apartments located on the same floor as the "exposed" ones can not be considered as an"unexposed", taking into account the measured values of the magnetic field.…”
Section: Discussionmentioning
confidence: 99%
“…We calculated sensitivity and specificity of a binary exposure classification, as previously performed by others. 8,9 We applied cutoffs of 0.2 and 0.4 mT to the measurements, and calculated sensitivity and specificity of 'high' exposure classification versus 'medium' or 'low'. All data were analyzed using Stata (version 10; StataCorp, College Station, TX, USA).…”
Section: Data Management and Statistical Analysismentioning
confidence: 99%
“…6 However, for this approach to work, it would be preferable if it were possible to group exposure of children to magnetic fields into high or low levels without monitoring, but based solely on location of the apartment relative to the transformer room within the building. In Finland, 7 Switzerland, 8 Israel 9 and Hungary, 10 spot measurements of magnetic field exposure have been performed in buildings with in-built transformers. These studies showed that exposure levels in apartments directly on top or adjacent to a transformer room were between 0.3 and 1 mT; well in line with what can be encountered in the vicinity of high-voltage power lines.…”
Section: Introductionmentioning
confidence: 99%